1995
DOI: 10.1002/aoc.590090409
|View full text |Cite
|
Sign up to set email alerts
|

Biocidal organotin compounds: Part 1. Preparation and characterization of triorganotin(IV) 4‐pyridyl‐ and 2‐pyrimidyl‐ thioacetates and the crystal structure of triphenyltin(2‐pyrimidylthioacetate)

Abstract: The preparation and spectroscopic character-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…On the other hand, it is noticeable that each pmta – acts as a tris‐dentate ligand rather than as a tetradentate observed in 2 , using one sulfur atom and oxygen atom in the carboxylate group to chelate one Ag I node into a distorted five‐membered heterocyclic ring, tilting about 78° to the adjacent pyrimidine ring, which suggests the twisted nature of the pmta – ligand as depicted in Figure 1. Obviously, the carboxyl group in 1 features a rare symmetry μ‐carboxylato‐O [Ag–O = 2.2813(18), 2.4847(19) Å] bridge, in agreement with the independent IR data with a Δ ν [ ν as (COO) – ν s (COO)] value of 296 cm –1 ,7 whereas in 2 , the carboxyl group shows a cis , trans ‐μ 2 coordination mode in agreement with the IR spectrum.…”
Section: Resultssupporting
confidence: 84%
“…On the other hand, it is noticeable that each pmta – acts as a tris‐dentate ligand rather than as a tetradentate observed in 2 , using one sulfur atom and oxygen atom in the carboxylate group to chelate one Ag I node into a distorted five‐membered heterocyclic ring, tilting about 78° to the adjacent pyrimidine ring, which suggests the twisted nature of the pmta – ligand as depicted in Figure 1. Obviously, the carboxyl group in 1 features a rare symmetry μ‐carboxylato‐O [Ag–O = 2.2813(18), 2.4847(19) Å] bridge, in agreement with the independent IR data with a Δ ν [ ν as (COO) – ν s (COO)] value of 296 cm –1 ,7 whereas in 2 , the carboxyl group shows a cis , trans ‐μ 2 coordination mode in agreement with the IR spectrum.…”
Section: Resultssupporting
confidence: 84%
“…Design and assembly of supramolecular architecture with variable cavities or channels are currently of great interest owing to their novel topologies and potential applications. Up to now, a great number of inorganic−organic hybrid coordination polymers have been synthesized based on covalent interactions or supramolecular connections such as hydrogen bond and/or π − π interactions. , It has been documented that the geometries of organic ligands have a great effect on the structural frameworks of such coordination polymers; thus, much effort has been devoted to modify the building blocks and to control the assembled motifs for required products through the selection of different organic ligands. Previous studies have shown that rigid bridging ligands containing multi-carboxylate groups (Scheme a,b) or hybrid pyridyl/carboxylate groups (Scheme c,d) are versatile ligands for construction of the moderately robust networks and other porous coordination polymers. However, much fewer studies on coordination chemistry of flexible organic ligands contemporarily containing carboxylate group and pyridyl nitrogen atoms (Scheme e) have been carried out. 6b, 4-Pyridylacetic acid (Hpya) possesses two interesting characteristics: (a) it possesses flexibility owing to the presence of a -CH 2 - spacer between the pyridyl ring and carboxylate moiety (Scheme e); (b) it holds three potential bonding sites, i.e., the nitrogen atom and two oxygen atoms of the carboxylate group. Because the carboxylate group can adopt monodentate, chelating-bidentate, bridging-bidentate, and bridging-multidentate modes, rich coordination modes of pya - may be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as a continuation of our previous studies of biological organotin(IV) chemistry (Chakrabarti et al 1995;Kamruddin et al 1996;Sen Sarma et al 2007), we undertook a detailed study, including field trials with some organotin(IV) compounds synthesised from bio-molecules. We wish to report here the syntheses and characterisation of four such new organotin(IV) compounds and the results of investigations of biocidal activity of these newly synthesised compounds together with four other reported organotin(IV) compounds, the syntheses of which were previously reported by us (Kamruddin 1996;Sen Sarma et al 2007).…”
Section: Introductionmentioning
confidence: 99%